Some polarisable force fields for molecular dynamics simulations of lipids, and bilayers. Issue 10 (2nd July 2016) - Guo, Wei; Cheng, Liwei; Chu, Huiying; Cao, Liaoran; Zhang, Depeng; Liu, Jiahui; Xu, Peijun; Zheng, Xuefang; Li, Guohui
Abstract: Molecular force fields (FFs) have an inherent difficulty in characterising electronic polarisation effects. In recent years, polarisable FFs were developed very quickly and have been used in a multitude of systems. In this article, we tried to represent the developments and applications of a number of polarisable FFs from several perspectives. Firstly, we reviewed the theories behind polarisable FFs to elucidate the advantages and disadvantages. Secondly, we describe some studies using polarisable FFs, ranging from water molecules to lipid membrane macromolecules. Finally, a brief development trend and perspective is given on rapidly growing polarisable FFs.